THE EFFECT OF CONCENTRATION AND LENGTH OF PEGAGAN LEAF SOAKING AGAINST THE QUALITY OF PORK MEAT REVIEWED FROM ORGANOLEPTIC TESTS - Sudipa, Putu Henrywaesa; Swacita, Ida Bagus Ngurah; Sukada, I Made; Sudimartini, Luh Made; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2020)
Almost all meat on the market is contaminated by microorganisms. As a result of the contamination of microorganisms, it changes in color, odor, and consistency. This research aims to study the effect of various levels of concentration and soaking time of Pegagan ( Centella asiatica L.) leaf juice and to study whether there is an interaction between concentration and soaking time of Centella asiatica L. juice on the quality of pork in terms of the organoleptic test. Soaking pork in the juice of Centella asiatica L. juice is done by inserting each piece of meat into eight glasses, which have been filled with control, 5%, 10%, and 15% concentration juice. Soaking is done for 5 minutes, and 10 minutes then the meat is drained for 15 minutes, then an organoleptic test is performed and analyzed by variance. The results of the concentration had a significant effect (P<0.05) on changes in color, odor, and consistency of meat. While the soaking time had a significant effect (P<0.05) on the smell of meat but no significant effect (P>0.05) on the color and consistency of pork. And also, there is no interaction between concentration and soaking time.